The Aboriginal people of the Monaro - Young, Michael; Mundy, Ellen; Mundy, Debbie ([Sydney] : NSW National Parks and Wildlife Service, 2000)
Overview of the Aboriginal people of the Monaro, from pre-European times to the 1990s, using official documents, journal articles, archaeological reports, oral histories and stories from individuals ; includes biographical information on individuals, a genealogy of the Mundy family, a listing of all the Monaro Aboriginal people recorded by G.A. Robinson and lists of people receiving blankets in 1834 and 1841.
Cover subtitle: A documentary history.
Includes index.
Bibliography: p. 358-363.
Keywords: Aboriginal Australians -- Social life and customs; Aboriginal Australians -- New South Wales -- Monaro; History; Race relations; History - Genealogy and family history; History - Oral history; Government policy - Initial period and protectionism; Social welfare - Rationing - Blankets and clothing; Monaro (S NSW SI55-16, SJ55-14); Cooma (Monaro, S NSW SJ55-04)